Grand timely topics in software engineering : International Summer School GTTSE 2015, Braga, Portugal, August 23-29, 2015, tutorial lectures /: International Summer School GTTSE 2015, Braga, Portugal, August 23-29, 2015, tutorial lectures. (2017) - Unknown
No abstract available